Analysis of willingness to pay (WTP) to support the sustainability of geotourism at Wediombo Beach, Gunung Kidul - Luthfatur Rohmah Nabilah; Harini Rika (E3S Web of Conferences, 2023)
The increase in tourism activities in the geotourism area of Wediombo Beach have triggered a cascade of effects, including economic growth and environmental degradation. To mitigate further environmental harm and support its preservation, financial backing is essential, particularly as this area is part of the UNESCO Global Geopark Gunungsewu. This research investigates the Willingness to Pay (WTP) of visitors at Wediombo Beach, seeking to determine their willingness to contribute to environmental protection and analyzing the factors influencing their WTP. The approaches used in this study are Contingent Valuation Method (CVM) and Travel Cost Method (TCM) to calculate WTP, utilizing multiple linear regression analysis to assess the impact of independent variables on WTP. This study uses multiple linear regression analysis to determine the effect of the independent variable on WTP. Through interviews conducted with 67 respondents of accidental sampling using the bidding game dichotomous question method.The findings reveal that Wediombo Beach is currently undervalued, as the average WTP to support the sustainability of geotourism at the site is IDR15,615.00 per individual per visit, totaling IDR99,782,308.00. The key factors influencing visitors to the WTP at Wediombo Beach are perceived attractiveness and educational value.